Crude Oil Price Differentials and Differences in Oil Qualities : A Statistical Analysis - Bacon, Robert (World Bank, Washington, DC, 2014)
This report updates and extends previous work by a statistical analysis of the relationship between crude price differentials and three quality differentials, as well as transport costs and seasonal effects. In addition to the API (American Petroleum Institute) gravity number and the sulfur content of the crudes, which are the qualities generally included in existing analysis, the report presents the impact of acidity (measured by the Total Acid Number - TAN) on the price differential. This is because acidity has become increasingly important as the volume of high acid crudes, particularly from West Africa, has steadily increased in recent years.